Zinc Serum Levels as A Protective Factor in Type 2 Lepra Reaction in Patients with Leprosy in East Nusa Tenggara, Indonesia - Christa Adelia Suvianto; Mikhael Tjahjady (GLOBAL HEALTH SCIENCE GROUP, 2024)
Leprosy, caused by Mycobacterium leprae, can lead to severe inflammatory reactions, known as type 2 reactions or erythema nodosum leprosum (ENL). Zinc, a crucial micronutrient for immune function, may influence the incidence of these reactions. This study investigates the relationship between serum zinc levels and the occurrence of type 2 reactions in leprosy patients in East Nusa Tenggara, Indonesia. Objective: To assess whether low serum zinc levels are associated with an increased risk of type 2 reactions in leprosy patients in East Nusa Tenggara.Method: A prospective cohort study was conducted involving leprosy patients at health centers and hospitals in East Nusa Tenggara. Serum zinc levels were measured using atomic absorption spectrophotometry. Patients were monitored for the development of type 2 reactions over a 12-month period. Data were analyzed using descriptive, bivariate, and multivariate statistical methods to explore associations between zinc deficiency and type 2 reactions. Results: The study found a significant association between low serum zinc levels and an increased risk of type 2 reactions. Patients with deficient zinc levels were more likely to experience severe inflammatory responses compared to those with normal zinc levels. Multivariate analysis confirmed that zinc deficiency was an independent risk factor for the occurrence of type 2 reactions. Conclusions: Zinc deficiency is linked to an increased risk of type 2 reactions in leprosy patients. Addressing zinc deficiency through supplementation could be an effective strategy to reduce the incidence and severity of these reactions. Incorporating zinc status assessments into leprosy management programs may improve patient outcomes and help control disease complications.